Friction Welding of Aluminium and Aluminium Alloys with Steel - Andrzej Ambroziak; Marcin Korzeniowski; Paweł Kustroń; Marcin Winnicki; Paweł Sokołowski; Ewa Harapińska (Advances in Materials Science and Engineering)
The paper presents our actual knowledge and experience in joining dissimilar materials with the use of friction welding method. The joints of aluminium and aluminium alloys with the different types of steel were studied. The structural effects occurring during the welding process were described. The mechanical properties using, for example, (i) microhardness measurements, (ii) tensile tests, (iii) bending tests, and (iv) shearing tests were determined. In order to obtain high-quality joints the influence of different configurations of the process such as (i) changing the geometry of bonding surface, (ii) using the interlayer, or (iii) heat treatment was analyzed. Finally, the issues related to the selection of optimal parameters of friction welding process were also investigated.